EM Modelling Considerations for mm-Wave On-Chip Antennas. Issue 1 (February 2020) - Sagouo Minko, Flavien; Stander, Tinus
Abstract: We investigate the inaccuracy of resonant frequency ( f0 ) estimation incurred by some common simplifications in electromagnetic (EM) simulation of mm-wave on-chip antennas. Using an 88 GHz patch antenna as a device under test (DUT), it is found that using a 2.5D planar EM solver produced highly inaccurate results. Including the bulk silicon and thin nitride in the model stack effected an improvement of 0.8% in estimating f0, while replacing individually modelled via arrays with equivalent blocks, and accounting for the etch factor, marginally improved both the estimation of f0 and reflection coefficient |S11 |. It is shown that, with the correct modelling choices, the error in f0 can be reduced to below 50 MHz at E-band, which is within the measurement variation of 880 MHz.